Rapid evaluation of probable recoverable reserves in tight reservoirs: a case study of Chang 8 reservoir (eighth member of Yanchang Formation) in Honghe oil field - Mingli GUO; Yan CHEN; Zhenheng ZHENG; Jun LI; Lian YU; Liqong LIU (Shiyou shiyan dizhi, 2021)
Tight oil reservoirs are featured by tight formations, large oil area, locally enriched "sweet spots", complex oil-water distribution, and complicated reservoir conditions brought by later engineering transformation, which determines the development performance of single well. The distribution of recoverable reserves has great variability and uncertainty, so it is difficult to obtain a reasonable and definite understanding using conventional reserve evaluation methods. By introducing the evaluation methods of unconventional shale oil and gas reserves in North America, the developed wells were used to determine the reserves of single wells, and the probability distribution characteristics of reserves of developed wells were used to characterize the reserves of blocks or reservoirs. The Chang 8 (the eight member of Yanchang Formation) tight and ultra-low permeability reservoir in the Honghe oil field was studied. The initial production performance and production decline characteristics of a single well were tracked, and the correlations between recoverable reserves and geological characteristics, oil-bearing properties and initial production performance were analyzed to determine the key factors affecting the estimation of recoverable reserves. The P10/P90 values were used to judge the uncertainty of the estimates. The minimum sample size required for 90% confidence can be obtained when the value is 3-8; if the value is greater than 10, it indicates that the reservoir has the complexity of geological and engineering transformation and the difference of different blocks. The key influencing parameters and the probability distribution of recoverable reserves of single well were established by using the uncertainty method, and the rapid evaluation of recoverable reserves of a single well were realized.